Review of the Flexible Credit Line, the Precautionary and Liquidity Line, and the Rapid Financing Instrument. (Policy Papers; Policy Paper, 2014)
This review of the Flexible Credit Line (FCL), the Precautionary and Liquidity Line (PLL), and the Rapid Financing Instrument (RFI) focuses on four key issues: (i) the demand for the FCL and PLL in the context of the broader role of the Fund's lending (including precautionary) instruments in the global financial safety net (GFSN); (ii) the qualification/conditionality framework for the FCL and the PLL; (iii) concerns about repeated usage of FCL arrangements by the same members and consideration of ways to further improve the transparency in the discussion of access/exit in the underlying staff documents; and (iv) the lack of demand for the RFI.